Continuous fabrication of multi-stimuli responsive graphene oxide composite hydrogel fibres by microfluidics. Issue 31 (31st March 2017) - Peng, Li; Liu, Yan; Gong, Jinghua; Zhang, Kaihuan; Ma, Jinghong
Abstract : Stimuli responsive graphene oxide composite hydrogel fibres were prepared via a microfluidic spinning process, and exhibit both thermo-triggered volume-phase transitions and electrically triggered bending behaviours. Abstract : Microfluidics appeared in the 1990s as a promising technology and has received considerable attention in developing stimuli-responsive hydrogel fibres in microscale for tissue engineering and actuation devices. In this work, thermo- and electro-responsive graphene oxide/poly( N -isopropylacrylamide)/sodium alginate (GO/PNIPAM/SA) hydrogel fibres were prepared via microfluidics and off-chip free radical polymerization. The composite hydrogel fibres were characterised using FTIR, SEM, and DSC. The thermo-triggered volume-phase transition and electrically triggered bending behaviours were also investigated. The results show that the hydrogel fibres have porous internal structures and the pore size becomes smaller with the increase of GO content due to the hydrogen bonding between the amide groups of PNIPAM chains and oxygen-containing groups on the GO nanosheets. Besides this, the incorporation of increased GO content enlarges the swelling ratio of the hydrogel fibre. The hydrogel fibres also exhibit bending behaviour under the non-contact direct current electric field.